Los debates del giro ontológico en torno al naturalismo moderno - Daniel Ruiz Serna (Revista de Estudios Sociales, 2016)
The ontological turn assembles a set of different perspectives that coincide in their interest in offeringalternatives to the nature/culture divide that has been the hallmark of modern naturalism. By calling into question what we conceive of as real, these perspectives vindicate alternative ways of interpreting the articulations between the natural and the cultural, and on that basis they pose interesting challenges for understanding social relations in the contemporary world. In the field of socioenvironmental conflicts, some lines of thought in political ecology insist that “conflicts of cultural distribution” cannot be easily evaded. In this sense, the ontological turn offers conceptual keys that can help to understand how such conflicts emerge. The article takes a synthetic approach to the work of some authors who are considered outstanding exponents of the ontological turn, many of whom are linked to the field of anthropology, and it offers a general and introductory, albeit not exhaustive, cartography of this useful turn for those who are beginning to look into this field of analysis.